Analisis Ketelitian Perhitungan Tonase Stockpile Batubara Hasil Pengukuran Metode RTK Radio GNSS dengan Teknik Akuisisi Data secara Point to Point dan Auto Topo - Farouki Dinda Rassarandi; Silvester Sari Sai; Hery Purwanto (JURNAL INTEGRASI, 2015)
Tonnage of Coal Stockpile can be decided by three aspect, there are from weighting, bardging and surveying. Tonnage measuring of coal stockpile with RTK Radio GNSS can be applied for surveying aspect. In the stockpile survey with RTK Radio GNSS, that implementation must be fast and accurate. Automatic measuring is one method of data acquisition for the best solution of efficiency. The purpose of this research is to inspect about data quality concerning DTM and accuration of tonnage calculations from RTK survey with two different met hods of data acquisition, there are Point to Point (manual measuring) and Auto Topo (automatic measuring). This research have held in Stockpile of CPP Buhut and Paringlahung (PT. TOP) in Central Borneo. The measuring methods of tonnage calculations from RTK Radio GNSS Survey with Point to point (May 2012) and Auto Topo (September 2013) data acquisitions. The volume calculated by cut and fill method from the DTM model of RTK Radio GNSS Surveying, then tonnage calculated by multiple of volume and coal density . After that, data analysis conducted by comparing tonnage data from surveying and weighting in each data acquisitions methods. The comparison result must be reference from the spesifications of ASTM’s standard, that tolerance is 2.95%. The result of tonnage survey calculations with Point to Point and Auto Topo data acquisition in CPP Buhut and Paringlahung has differences concerning tonnage from weighting, there are 1.04% in CPP Buhut and 1,07% in Paringlahung with Point to Point data acquisition, and also -1.14% and -1.16% in the same location with Auto Topo. That result indicated indeed both of them data acquisition methods fulfil ASTM requirements. In this conclusion, RTK Radio GNSS methods with Point to Point and Auto Topo data acquisition are indicating reached spesification in stockpile survey.